Multidrug-resistant antibacterial activity and active compound analysis several types of seaweed from Karimunjawa, Jepara. Issue 1 (July 2020) - Susanto, A.B.; Ari Setyati, Wilis; Pramesti, Rini; Pringgenies, Delianis; Zainuddin, Muhammad
Abstract: Pathogenic bacteria that recently infect humans have been undergone an evolution. The evolution of treatment measures is not in accordance with the dose. Several cases in hospitals have found multi-type bacterial drug resistance. These cases affected much death of the patient. Therefore, this study explores the seaweed from the Karimunjawa Islands, Jepara as the potential sources of new antibacterial active compounds. The study is conducted in the laboratory and used the experimental design of sampling, extraction, resistance test, antibacterial extract test, and analysis of extract active compounds. There are three types of seaweed sampled: S. crassifolium, Padina australis and Dictyota dichotoma. Each extraction is carried out with diethyl ether, methanol, ethanol and chloroform solvents. This study used pathogenic bacterial isolates: Pseudomonas aeruginosa, Staphylococcus epidermidis, Staphylococcus aureus and Escherichia coli which are tested with 13 antibiotics. The resistance test showed the value of multiple antibiotic resistance index (mar) of 0.84; 0.76; 0.48 and 0.34. Antibiotics with a high percentage resistance value (100%) are from groups of lipopeptides (colistine sulfate) and (3-lactams groups (ampicillin). The seaweeds extract tested for antibacterial activity at different concentrations. The results showed that different types and concentrations of extracts had different antibacterial activity values (p <0.05). The extract with high antibacterial activity is an extract from seaweed S crassifolium with methanol solvent. The extract contained phenol 12 mg/g, flavonoid 1.6%, tannin 0.63%, fucoxanthin 0.59 mg/g, carotenoid 165.9 g/g, chlorophyll-a 0.92 mg/g and chlorophyll-b 0.28 mg/g.